(untitled) (Research, Society and Development, 2020)
Creole varieties have a wide range of colors, morphology and uses. The preference for using grains or creole seeds can be attributed to characteristics such as adaptability, valuing customs, taste and quality, in addition to the low cost of production. The objective of the study was to develop cookies formulated with creole grains of corn, beans and pine nuts and to evaluate their proximal and bioactive composition, in addition to assessing the sensory profile of these products. The Temporal Dominance of Sensations analysis indicated that cookies had a pleasant flavor and crispness, positive attributes for consumers of these products. The results of proteins and fibers indicated levels of 11% and 6.4% respectively, which defines this food as a source of these compounds. The moisture content (5.3%) was satisfactory, as it demonstrates a longer shelf life for cookies. The antioxidant activity found by the DPPH and ABTS methods revealed that cookies have the ability to reduce free radicals. Thus, cookies made with creole grains and pine nut starch have great potential as a bakery product, in addition to adding value to food from regional family farming.